Differential responses in first birth behaviour to economic recession in the United Kingdom - Mark Lyons-Amos; Ingrid Schoon (Journal of Biosocial Science, 2018)
Economic conditions have dramatic influences on fertility. This paper evaluates the effect of the 2008 `Great Recession' in the UK on first birth rate, which is the fertility behaviour most susceptible to external economic conditions. The key aim of the study was to assess the effect of the recession on fertility by individual-level characteristics, enabling variation in responses to economic hardship to be observed. Data were from the nationally representative UK Household Longitudinal Study (UK-HLS). Cumulative transition models were used to model the probability of first birth for women between the ages of 17 and 30 in three UK birth cohorts. The effect of the recession was captured using direct measures (local unemployment rates and individual unemployment status) and a pre-/post-comparison, capturing indirect effects. In general, higher birth rates were observed among more disadvantaged women compared with advantaged groups. The effect of the recession was disaggregated by social strata; the overall effect was counter-cyclical although at a slower rate among disadvantaged women.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330